Reversal of Arterial Stiffness in Patients with Primary Aldosteronism after Treatment. (June 2015) - Liao, Che-Wei; Chen, Ying-Hsien; Wu, Xue-Ming; Chang, Yi-Yao; Liao, Min-Tsun; Wu, Vin-Cent; Liu, Kao-Lang; Chueh, Shih-Chieh; Ho, Yi-Lwun; Wu, Kwan-Dun; Lin, Yen-Hung
Abstract : Background: Primary aldosteronism (PA) is one the most common cause of secondary hypertension. Exposure to excessive aldosterone leads to various complications on cardiovascular system, and some are reversible after treatment, such as hypertension, left ventricular hypertrophy and even arterial stiffness. However, the time course of arterial stiffness reversal and the predicting factors on PA patients are still unclear. Method: We prospectively collect aldosterone producing adenoma (APA) patients from March 2006 to January 2012. We measured the right brachial-ankle pulse wave velocity (PWV) to represent arterial stiffness. All patients were followed 6 months and 12 months after operation. Results: Total 108 patients were included in this study with 62 female and 46 male. The pre-treatment PWV averaged as 1642.44 ± 317.892 cm/s. After correlation and multi-variable linear regression analysis, age, duration from diagnosis of hypertension to enrollment, and baseline systolic blood pressure are the determinant factors to baseline PWV. After treatment, the patients' PWV decreased significantly during the first 6-month (1543.08 ± 288.799 at 6-month, p  < 0.001)but not significant during the latter 6 month (1578.83 ± 337.745 at 12-month, p  = 0.155). After correlation study and multi-variable regression analysis, the decrement of diastolic pressure (ΔDBP) and the baseline PWV correlated most significantly with PWV decrement (ΔPWV). Conclusion: The arterial stiffness of APA patients could be reversed after treatment. The determinant factors of baseline PWV included age, duration of hypertension and baseline systolic pressure. The determinant factors of ΔPWV are baseline PWV and ΔDBP.